Variasi Bahasa Kaum Milenial: Bentuk Akronim dan Palindrom dalam Media Sosial - Syihaabul Hudaa; Ahmad Bahtiar (ESTETIK : Jurnal Bahasa Indonesia, 2020)
Modernity makes language develop quickly, one of which is the emergence of new vocabularies of Indonesian language. The meanings of vocabularies that emerge are often not understood, thus making the communication process not conveyed. One of the contributors to the fastest development of language is millennial generation. Millennials use various languages in communication on social media. However, the language that arises sometimes has a negative meaning and is included in the classification of slang. It is interesting to study that the Indonesian language is able to absorb, match, and bring up new terms in communication. The purpose of this article is to discuss the emergence of new vocabularies in a variety of social media. The emergence of new vocabularies is reviewed from two aspects, namely positive aspects and negative aspects. In addition, the words that appear are reviewed from the wrong form of acronyms or palindromes. The methodology used in this study is included in the descriptive qualitative type by describing the findings of the study using words in detail. Data collection uses content analysis by linking to phenomena in the community. Anchored in the data, it is revealed that millennial generation tends to use slangs in the wrong form of acronyms and palindromes. Because correct palindromes read from the back or front have the same words and meanings. In contrast, millennial generation makes writing in the form of a palindrome as mereslang vocabularies without knowing the correct concept of the palindrome